Effect of Zn/ZnO integration with hydroxyapatite: a review. (28th January 2018) - Saxena, Varun; Hasan, Abshar; Pandey, Lalit M.
Abstract: Hydroxyapatite (HAp) is one of the most studied ceramic for various biomedical applications such as bone tissue engineering, biologicals delivery systems and bioactive coatings. It owns extensive biocompatibility. However, lower mechanical properties for load bearing applications, lower antimicrobial activity and lower biological interaction rates are the major lags for biomedical applications of HAp. Various researchers have tried to integrate HAp with various metals and metal ions to overcome these holdups. In this review, we have described the crystal structure of both HAp and zinc oxide (ZnO) and have majorly focused on the zinc and ZnO integration with HAp. Zn/ZnO offer several physical and biological properties. We have evaluated the effect of zinc integration over physical state and mechanical properties of HAp with latest research examples. We have appraised the additional biological properties provided by the incorporation zinc into the HAp through recent examples of researchers with varying degree of successes.